Exploring soil erodibility: integrating field surveys, laboratory analysis, and geospatial techniques in sloping agricultural terrains - Soniari, Ni Nengah; Trigunasih, Ni Made; Sumarniasih, Made Sri; Saifulloh, Moh (Brawijaya University, 2024)
The escalating trend of land degradation poses a significant challenge, especially in sloping agricultural terrains, driven by the increasing global demand for food and the limited availability of flat arable land. In response to these challenges, farmers are compelled to shift their focus towards cultivating sloping terrains. This research aimed to employ a comprehensive methodology that integrates on-site field surveys, meticulous laboratory soil analyses, and geospatial data for mapping soil erodibility. The parameters under scrutiny encompass various crucial aspects, including soil texture (ranging from coarse sand to very fine sand, silt, and clay), soil structure, organic matter content, and permeability. The meticulous examination of these factors serves as the foundation for calculating soil erodibility, utilizing the well-established Wischmeir and Smith formula developed in 1978. The research findings present a nuanced understanding of soil erodibility in the study location, revealing a spectrum spanning low to very high erodibility. Specific units, such as Unit 1, Unit 2, Unit 3, Unit 7, Unit 9, Unit 10, Unit 13, and Unit 16, exhibit very low to low erodibility. In contrast, Unit 4, Unit 6, Unit 14, and Unit 15 showcase moderate erodibility, while units like Unit 5, Unit 8, Unit 11, Unit 12, Unit 17, and Unit 18 are characterized by moderately high to very high erodibility. These insightful results shed light on the diverse erodibility levels within the studied locations and provide valuable guidance for formulating sustainable land management practices.